Advancing a New Generation of Sustainability-Based Assessments for Electrical Energy Systems: Ontario as an Illustrative Application—A Review - F. Ignacio Aguilar; Robert B. Gibson (Energies, 2023)
Negative social and ecological trends are putting essential life-support systems at risk. Necessary responses include sustainability transformations in diverse sectors to enhance the planetary capacity to deliver more positive effects to all. Sustainability-based assessment frameworks are tools to guide the evaluation of initiatives in different human sectors and promote decisions that enhance overall social and ecological well-being. However, advancing sustainability remains difficult, in part because it must be pursued in a world of complex interactions and must respect the specifics of each case and context. This paper reports the process of building a sustainability-based assessment framework for electrical energy systems carried out by Aguilar. This work further specified the framework for electrical energy systems for application in the case and context of the electrical energy system in the Canadian province of Ontario. The illustrative application revealed that Ontario’s electrical energy system has made some progress towards contributions to sustainability but requires improved efforts to be on a path to adequate transformation. The research found that the sustainability-based assessment framework for electrical energy systems is promising and well-suited for further application to particular electricity-related initiatives. However, more applications are needed to further test the utility of the framework and refine the proposed criteria.